2023
DOI: 10.7759/cureus.36717
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Low Birth Weight in India: Findings From a Nationally Representative Cross-Sectional Survey (2019-21)

Abstract: Introduction: Low birth weight (LBW) is an important public health indicator extensively linked to infant and child mortality, especially in lower-middle-income countries (LMICs). Globally, 15.5% of all infants are born with LBW while 95% of these occur in LMICs. This study aims to examine the prevalence and determinants of LBW in India.Methods: Data were obtained from the fifth National Family Health Survey (NFHS) round conducted during 2019-2021. The study sample included women aged 15-49 years who had a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Of the 4,710 newborns born during the study period, 327 (6.9%) weighed less than 2.5 kg, which is in line with the 15% to 30% reported prevalence of LBW in India, likely reflecting socioeconomic and regional disparities [1,6]. The study found that 55.6% (182 out of 327) of LBW newborns were SGA and preterm, while 22.6% (74 out of 327) were full-term SGA.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Of the 4,710 newborns born during the study period, 327 (6.9%) weighed less than 2.5 kg, which is in line with the 15% to 30% reported prevalence of LBW in India, likely reflecting socioeconomic and regional disparities [1,6]. The study found that 55.6% (182 out of 327) of LBW newborns were SGA and preterm, while 22.6% (74 out of 327) were full-term SGA.…”
Section: Discussionsupporting
confidence: 75%
“…In India, the prevalence of LBW ranges from 15% to 30%, with notable regional variations [6,7]. Despite advancements in neonatal care, LBW remains a significant contributor to infant mortality and morbidity in the country, accounting for 60-80% of all neonatal deaths nationwide [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several individual-level and household-level variables were identified as potential covariates of LBW 39 , 40 , anaemia 41 and ARI 42 . These variables were included in the analysis based on their significance with the respective health outcome.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of newborns with LBW had a very small decline from 17.5% (17.19, 17.80) in NFHS-4 (2015-16) to 17.29% (17.01, 17.57) in NFHS-5 (2019-21). [ 5 ] India has made considerable progress in reducing the LBW of children during the past decade, and it remains a leading cause of child mortality in the country, especially among socio-economically disadvantaged groups. To achieve the target of the Sustainable Development Goal (SDG) in infant and under-5 mortality levels by 2030, an accelerated improvement is still required in reducing the occurrence of LBW.…”
Section: Introductionmentioning
confidence: 99%